Efficient deep blue fluorescent emitter showing high external quantum efficiency. (September 2015) - Cha, Seung Ji; Han, Noh Soo; Song, Jae Kyu; Park, So-Ra; Jeon, Young Min; Suh, Min Chul
Abstract: A benzoanthracene-cored deep blue-emitting compound, N 6, N 9 -bis(4-cyano-phenyl)- N 3, N 9 -diphenylspiro[benzo[ de ]anthracene-7, 9′-fluorene]-3, 9-diamine was synthesized and which has an exchange energy of ∼0.2 eV between the singlet and triplet state. OLED devices doped with this new deep blue emitter showed comparable device performances and delayed fluorescence via the reoccupation of the singlet excitons from the triplet excitons with long lifetimes. In particular, the 10%-doped device exhibited the maximum external quantum efficiency of 14.8% and current efficiency of 15.1 cd/A with Commission International de L'Edairge coordinates of (0.14, 0.11). Graphical abstract: Highlights: Highly efficient fluorescent blue OLED devices with new emitter materials. TTA behavior to realize a highly efficient deep blue fluorescent OLED. Effect of spiro-shaped molecules. Fluorescent OLED showing 14.8% of external quantum efficiency with (0.14, 0.11).